K-12 MODERN SCHOOLS IN SERBIA: EXPLORATORY RESEARCH REGARDING TEACHERS GENUINE KNOWLEDGE AND PERCEPTION OF AI-BASED OPPORTUNITIES AND CHALLENGES IN EDUCATION - Kuleto, Valentin; Ilic, Milena; Bucea-Manea-Țoniş, Rocsana; Živanović, Zorana; Păun, Dan (Journal of Economic Development, Environment and People, 2022)
LINK Educational Alliance (LEA is an educational group based in the Republic of Serbia which involves privately owned providers of formal and informal education, the format for the development of Educational Technologies services and Business support for their business. The exploratory research was conducted among K-12 teachers among a total population of 152 and a sample of 77 respondents (50.66%) to provide information about the perception of the teachers towards implementation of the Artificial intelligence-based solutions and the opportunities and challenges that artificial intelligence (AI) will bring into their daily activities, as well as their genuine knowledge about AI. For data analysis, we used SmartPLs Software version 3.0, making inferential and variable association analyses. The teaching process, based on the opinion of K-12 teachers regarding activities that might be automatised through AI implementation in the educational process, supported by their level of awareness and knowledge about AI. For example, AI offers opportunities to automate specific strategies and activities, which would achieve better organisation of teachers' working time and productivity and increase the share of time that teachers spend "directly interacting with students" is the central hypothesis whose validity is tested. The aim of this study is to provide adequate model for testing AI attitudes in K-12 level of education in Republic of Serbia, among teachers in elementary and secondary schools.